2002
DOI: 10.1016/s0960-9822(02)00809-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tissue-Specific MicroRNAs from Mouse

Abstract: MicroRNAs (miRNAs) are a new class of noncoding RNAs, which are encoded as short inverted repeats in the genomes of invertebrates and vertebrates. It is believed that miRNAs are modulators of target mRNA translation and stability, although most target mRNAs remain to be identified. Here we describe the identification of 34 novel miRNAs by tissue-specific cloning of approximately 21-nucleotide RNAs from mouse. Almost all identified miRNAs are conserved in the human genome and are also frequently found in nonmam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

71
2,341
4
16

Year Published

2003
2003
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 3,045 publications
(2,474 citation statements)
references
References 23 publications
71
2,341
4
16
Order By: Relevance
“…In the case of miR-375, expression of this miRNA has been reported in numerous tissue types including the pituitary gland, adrenal gland, intestine, lung, and several types of cancer [9] [10]. Similarly, miR-7 and miR-184 have been shown to be highly enriched in the central nervous system and eye, respectively [11]. Recent studies using mouse knockouts have shown that loss of these three abundant miRNAs will increase β-cell exocytosis however it still remains unclear whether all miRNAs present in the β-cell are committed to an identical functional role and whether they perform the same function in all cell types where they are present [12] [9] [8].…”
Section: Microrna Profiling In the Pancreatic β-Cell And Isletsmentioning
confidence: 99%
“…In the case of miR-375, expression of this miRNA has been reported in numerous tissue types including the pituitary gland, adrenal gland, intestine, lung, and several types of cancer [9] [10]. Similarly, miR-7 and miR-184 have been shown to be highly enriched in the central nervous system and eye, respectively [11]. Recent studies using mouse knockouts have shown that loss of these three abundant miRNAs will increase β-cell exocytosis however it still remains unclear whether all miRNAs present in the β-cell are committed to an identical functional role and whether they perform the same function in all cell types where they are present [12] [9] [8].…”
Section: Microrna Profiling In the Pancreatic β-Cell And Isletsmentioning
confidence: 99%
“…5 The focus of the current study is miRNA 155 (miR-155), which is located on chromosome 21 and is transcribed from the B-cell integration cluster. 6 In addition to its involvement in proinflammatory responses, recent evidence indicates that this miRNA has a significant role in the process of carcinogenesis of several solid tumors, including colon cancer, 7 breast cancer, 8 and pancreatic ductal adenocarcinoma. 9 Recently, Tili et al reported that miR-155 can act as a mutator and, together with an miR-155-linked inflammatory environment, may be a potential mechanism connecting inflammation and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs also appear to have important roles in the mammalian central nervous system (CNS). Numerous miRNAs are expressed in the CNS [22][23][24], and many neural miRNAs are expressed in spatial and/or temporal patterns that suggest roles in the regulation of CNS development [25][26][27][28][29][30]. MiRNA miR-132 has been shown to regulate neuronal morphogenesis through decreasing levels of GTPase-activating protein, p250GAP [31] and (along with miR-219) has been implicated in the regulation of circadian rhythms [32].…”
Section: Introductionmentioning
confidence: 99%